SELF CONCEPT OF PEOPLE WITH BIPOLAR THROUGH BIPOLAR SURVIVAL GROUP IN DENPASAR - Putri Ekaresty Haes; Ni Putu Dinda Haryanti (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2022)
Daily routine can trigger stress and load of though that make mood changes, mood changes are normal, for physical and mentally healthy human but not so with ODB (people with bipolar). The focus of this study is communication of bipolar survivor group in Denpasar that supports healing from ODP (people with bipolar). This research is qualitative research using case study approach, with only focuses on group communication in only one group of bipolar survivors in Denpasar. Data collection technique used participatory observation, in-depth interviews with informants and documentation techniques. This study uses data triangulation as a technique for validity of the data. The result obtained from this study show that ODB (people with bipolar) are greatly helped by the presence of bipolar group of survivors, so that emotion bond are established between members and have the same goal, namely recovering from mental illness. In addition, this group also help its member find the self-concept of its members, so that its members have a new life to rejoin the society.Keywords: Group Communication, Bipolar, Self Concept